Форми здійснення громадського контролю за діяльністю Національної поліції - Василенко, В. М.; Vasylenko, V. M.; Viktor Vasylenko (Європейські перспективи. - 2020. - № 1. – С. 220-226, 2020)
Проаналізовано основні форми здійснення громадського контролю за діяльністю Національної поліції та визначено їх особливості. Запропоновано під формами громадського контролю за діяльністю Національної поліції розуміти нормативно урегульоване зовнішнє вираження контрольних дій представників громадянського суспільства по оцінці та реагуванні на відхилення у діяльності органів поліції та порушення поліцейських. Розглянуто форми громадського контролю за діяльністю поліції, виходячи з їх специфіки та правових підстав реалізації.

The main forms of public control over the activities of the National Police are analyzed and their features are determined. It is proposed to understand the forms of public control over the activities of the National Police as a normatively regulated external expression of control actions of civil society representatives to assess and respond to deviations in the activities of police bodies and violations of police officers. Forms of public control over the activities of the National Police are characterized by the following features: 1) external expression of the activity of the subjects of public control over the activities of the National Police; 2) are based on legal principles of general and special nature; 3) constitute only a part of the legally defined content of “public control of the police” and at the same time find their expression in other norms of the Law of Ukraine “On the National Police”; 4) a number of special administrative and legal provisions need to be adjusted to bring them in line with the content of such forms. Forms of public control over police activities, based on their specifics and legal grounds for implementation, it is proposed to divide into two main blocks: 1) general forms of public control over police activities: appeals of citizens, public associations and legal entities; request for information; public examination; public consultations; public monitoring (audit); 2) special forms of public control over the activities of the police: the interdependence of reporting on police activities and its evaluation; adoption of a resolution of no confidence in the heads of police bodies; public participation in the consideration of complaints about the actions or inaction of police officers; participation of public representatives in the work of police commissions for selection (competition) and promotion of police officers.

Проанализированы основные формы осуществления общественного контроля за деятельностью Национальной полиции и определены их особенности. Предложено под формами общественного контроля за деятельностью Национальной полиции понимать нормативно урегулированное внешнее выражение контрольных действий представителей гражданского общества по оценке и реагированию на отклонения в деятельности органов полиции и нарушения полицейских. Рассмотрены формы общественного контроля за деятельностью полиции исходя из их специфики и правовых оснований реализации.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Державне адміністративне управління. Адміністративна діяльність. State Administration. Administrative Activity. Государственное административное управление. Административная деятельность; Україна. Ukraine. Украина; Національна поліція України. National police of Ukraine. Национальная полиция Украины; National police of Ukraine; Национальная полиция Украины; поліція; police; полиция; контроль; громадський контроль; public control; общественный контроль; форми контролю; forms of control; формы контроля